METODE OPTIMASI PADA SISTEM PENGENDALIAN PROSES TANGKI PEMANAS BERPENGADUK - Rudy Agustriyanto (Talenta Publisher (Universitas Sumatera Utara), 2017)
In this research, PID (Proportional Integral Derivative) controller tuning was done using optimization method and the result was compared to the other well-known tuning methods (Direct synthesis, Ziegler– Nichols). The purpose of this research is to obtain the best output response when the set point and disturbance are changed. Tuning is a useful process to set the controller parameter that can affect the output response from the changing set point (servo problem) as well as from the disturbance (regulatory problem). The controller performance can be evaluated from the value of Sum Squares of Error when the system is controlled by PID controllers that is tuned with chosen method. The research result showed that optimization method was better than the other methods because it could give the best result.